Nabhi's manual for procurement of goods, services and works in government departments - Edited by Garg, Ajay Kumar (Delhi Nabhi Publications, 2023)
Manual for Procurement of Goods 2022 Manual for Procurement of Consultancy & other Services 2022 Manual for Procurement of Works 2022 CVC guidelines on Intensive Examination of Public Procurement Contracts 2022.
Keywords: Procurement of Goods Services and Works; Procurement in Govt. Departments